Examen especial a la cuenta efectivo y equivalentes de efectivo en el Consorcio de Transportistas Urbanos de la ciudad de Loja, en el periodo 2015 - Narváez Salinas, Lorena Yazmín (2018)
The thesis work entitled "SPECIAL REVIEW OF CASH AND CASH EQUIVALENTS IN THE CONSORTIUM OF URBAN TRANSPORTERS OF THE CITY OF SHOP, IN THE PERIOD 2015." It was developed in order to determine and know the veracity, legality and reasonableness Of its balances that in this way help the entity to improve its operations and activities that make it possible to increase the efficiency, effectiveness and economy of its operations. In order to fulfill the objectives, it was possible to analyze the economic movement of the Caja General Account, Caja Chica, Banks, began with the Planning phase, where information was obtained and authorization of the entity, in the Execution of Work where the Sufficient and competent information by applying audit evidence and practices in order to examine the items under study in the financial statements and to obtain conclusions related to the objectives of the special review, then the working papers were prepared with the information obtained; In the Communication on Results, the report was drawn up with due conclusions and recommendations. It is concluded from the evaluation of the internal control system that the level of confidence and risk is moderate and that compliance tests, such as substantive tests, were applied.